PENGARUH KARTU KUARTET TERHADAP HASIL BELAJAR DITINJAU DARI AKTIVITAS SISWA PADA MATA PELAJARAN PPKN DI KELAS II MI PSM SALAK GEMARANG - Maulidiyah, Faridah (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2025)
The purpose of learning media is to achieve learning objectives optimally. Observations at MI PSM Salak Gemarang, particularly in Grade II, show that classroom teachers still make minimal use of varied and innovative learning media during the learning process. This thesis discusses the effect of quartet card media on learning outcomes in terms of student activity—specifically, how and whether quartet card media affects learning outcomes in terms of student activity in the PPKN subject for Grade II at MI PSM Salak Gemarang. This research uses a quantitative research method with an experimental research design. The population and sample in this study are all Grade II students at MI PSM Salak Gemarang. Data collection techniques include tests and non-participant observation. The research instruments consist of tests—namely pretest and posttest—and observation, which is conducted when the learning media is applied during the learning process in the study. Data analysis involves several tests: instrument testing, prerequisite analysis tests, and hypothesis testing. The instrument test results show that 20 questions can be used, and the researcher used all of them for data collection. The prerequisite analysis tests include the normality test, homogeneity test, and N-Gain test. The normality test results show a pretest significance value of 0.636 > 0.05 and a posttest significance value of 0.495 > 0.05. The homogeneity test result shows a significance value of 0.412 > 0.05. The N-Gain test result is 0.3306. Finally, the hypothesis test is conducted using the t-test, which produces a sig. (2-tailed) value of 0.008 < 0.05. Thus, it can be concluded that Ho is rejected and Ha is accepted